The impact of the COVID-19 virus and pandemic on healthcare utilization, access, delivery, experiences, and outcomes in the spinal cord injuries/dysfunction population: A scoping review study. - Arrani Senthinathan; Stephanie Cimino; Susan B Jaglal; B Catharine Craven; Karen Tu; Sara Guilcher (PLoS ONE)
Background Individuals with spinal cord injuries or disease (SCI/D) require frequent healthcare services. The COVID-19 pandemic may have impacted healthcare. Furthermore, due to secondary health conditions and comorbidities persons with SCI/D are at increased risk of experiencing severe symptoms or outcomes if infected with the COVID-19 virus. It is unclear to what extent research has investigated the pandemic and virus impacts on the SCI/D population. Objective To identify and summarize what is reported in the literature on the impact the COVID-19 virus and pandemic had on healthcare, health outcomes, and experiences in the adult SCI/D population. Methods Electronic databases and grey literature were searched for articles that included an adult population with a SCI/D and investigated the impact the COVID-19 virus and pandemic had on healthcare-related outcomes and experiences. Articles were double screened, and data were extracted, and synthesized to provide a descriptive summary of the findings. Results Twenty-four studies were included in this review with eight qualitative, fifteen quantitative, and one mixed methods study. Sixteen studies investigated healthcare utilization/access; nine investigated care delivery, nine investigated patient outcomes, and eight investigated patient experiences, with multiple studies spanning different categories of investigation. The pandemic was detrimental to healthcare utilization, access, and outcomes, but no studies quantified these changes. Virtual care was well-received by the SCI/D population to maintain continuity of care. The SCI/D population had issues with maintaining caregiving support. It was unclear if the COVID-19 virus infection impacted individuals with SCI/D differently than the general population. Conclusions This scoping review found the pandemic negatively impacted multiple aspects of healthcare in individuals with SCI/D, however further investigation on health outcomes is required. More research, particularly large-scale quantitative studies, investigating healthcare access, utilization, and delivery, as well as patient outcomes and experiences is needed to improve care in the SCI/D population post-pandemic onset.